Association between health status and long‐term mortality after percutaneous revascularization of peripheral artery disease. Issue 6 (19th February 2016) - Bunte, Matthew C.; House, John A.; Spertus, John A.; Cohen, David J.; Marso, Steven P.; Safley, David M.
Abstract : Objectives: To explore the association of health status change and long‐term survival among patients with symptomatic peripheral artery disease (PAD). Background: Early gains in health status after successful endovascular therapy (EVT) for symptomatic PAD can be maintained up to 1 year. Whether such health status improvements are associated with long‐term survival benefits is unknown. Methods: Between February 2001 and August 2004, 258 patients with symptomatic PAD treated with EVT participated in a prospective study evaluating baseline and 1 year health status using the Peripheral Artery Questionnaire (range 0–100, higher scores = better). All‐cause mortality was assessed for all patients at a median of 9.4 years following EVT. Results: The mean age at enrollment was 68 ± 11 years; 61% were male, 97% were Caucasian, and 38% had diabetes. Patients with a clinically meaningful health status improvement (≥8 points) 1 year after their index procedure (79%) were identified as responders. Responders had a significantly better 10 year survival compared with nonresponders (60% vs 38%, p  = 0.025). Responder status was associated with a survival advantage that persisted in risk‐adjusted analysis (adjusted hazard ratio for long‐term mortality, 0.66 [95% CI, 0.45–0.97]; p  = 0.036). Conclusions: Among patients with symptomatic PAD undergoing EVT, improvement of PAD‐specific health status at 1 year follow‐up was associated with improved long‐term survival. Whether additional treatment for patients with poor response to EVT could improve long‐term survival warrants further investigation. © 2016 Wiley Periodicals, Inc.